A new Ladinian (Middle Triassic) mysidacean shrimp (Crustacea, Lophogastrida) from northern Italy and southern Switzerland. (March 2020) - Larghi, Cristiano; Tintori, Andrea; Basso, Daniela; Danini, Gianluca; Felber, Markus
Abstract: Since the end of the nineteenth century, many paleontological studies have been developed on the Middle Triassic localities of the Monte San Giorgio area (Canton Ticino, Switzerland, and Lombardy, Italy). These localities were inscribed in 2003 and 2010 in the UNESCO World Heritage List due to their paleontological relevance. New crustaceans are here described from the Kalkschieferzone member of the upper Ladinian Meride Limestone, outcropping near Besnasca-Cà del Frate (Viggiù, Italy) and Meride (Mendrisio, Switzerland). Several hundred specimens of a new genus and new species of Lophogastrida, named here Vicluvia lombardoae, improve information on Triassic mysidaceans (sensu lato), a group of shrimp-like crustaceans presently including hundreds of species worldwide distributed in marine and freshwater environments. The paper discusses the relations between Vicluvia n. gen. and the other fossil genera belonging to the same family. Vicluvia lombardoae n. gen. n. sp. exhibits two dorsally vanishing transverse grooves with their branches regularly bending toward the posterior margin of the shield and a telson with a rounded and setose apex. It was probably a euryhaline species living in a transitional environment affected by frequent and ephemeral salinity variations. Middle Triassic taphonomic windows have preserved specimens of lophogastrids in shallow basins along the Tethys, from the present Alps to China as well as in the German Basin. UUID: http://zoobank.org/1623e8f9-2ceb-4cd6-bcbe-4f05a873e1ff